Temporal and spatial resolution of the neutron probe for C/O nuclear well logging. (November 2022) - Batur, J.; Sudac, D.; Valkovic, V.; Meric, I.; Pettersen, H.E.S.; Nad, K.; Uroic, M.; Orlic, Z.; Perkovic, A.; Gacina, M.; Obhodas, J.
Abstract: The potential of detecting particular formation elements inside boreholes, separated by small distances, was investigated. Neutron probe, designed for C/O nuclear well logging and with associated alpha particle method (AAP) as its operational principle, was used. The measurements consisted of irradiating 0.5 l diesel-filled plastic bottle with fast tagged neutron beam. The bottle was placed in four positions along the axis of the probe, spaced by ∼ 10 cm; time spectrum for each position was obtained. The peaks in time spectra are separated by ∼ 2 ns, suggesting that neutron probe with AAP can, in principle, distinguish between parts of the formation separated by 10 cm. The results were confirmed by Monte Carlo (MC) simulations of the experiment.